You give more, I give more: “The impact of career growth on knowledge sharing behavior.” - Irma Suryani; Nidia Sofa (Proceedings of AICS - Social Sciences, 2017)
Knowledge sharing plays a significant role in enhancing innovation and creativity. Understanding what factors influence knowledge sharing among individuals in an organization has been widely studied, especially factors which derived from social exchange and psychological contract theory. However, how career growth affects knowledge sharing behavior in terms of psychological contract theory has not been studied in the previous literature. Therefore, this study aims to investigate career growth’s effect on knowledge sharing in an organization. The career growth is reflected from four elements; career goal progress, professional ability development, promotion speed, and remuneration growth. From 85 questionnaires distributed to lecturers and staffs at Syiah Kuala University, the results support the hypothesis stating that there is a significant relationship between organizational career growth and knowledge sharing behavior. Keywords:Organizational career growth, knowledge sharing behavior.